A Joint Action in Times of Pandemic: The German BioImaging Recommendations for Operating Imaging Core Facilities During the SARS‐Cov‐2 Emergency. Issue 9 (18th July 2020) - Dietzel, Steffen; Ferrando‐May, Elisa; Fried, Hans; Kukat, Christian; Naumann, Angela; Nitschke, Roland; Pasierbek, Pawel; Peychl, Jan; Rasse, Tobias Manuel; Schroth‐Diez, Britta; Stöckl, Martin Thomas; Terjung, Stefan; et al.
Abstract: Operating shared resource laboratories (SRLs) in times of pandemic is a challenge for research institutions. In a multiuser, high‐turnover working space, the transmission of infectious agents is difficult to control. To address this challenge, imaging core facility managers being members of German BioImaging discussed how shared microscopes could be operated with minimal risk of spreading SARS‐CoV‐2 between users and staff. Here, we describe the resulting guidelines and explain their rationale, with a focus on separating users in space and time, protective face masks, and keeping surfaces virus‐free. These recommendations may prove useful for other types of SRLs. © 2020 The Authors. Cytometry Part A published by Wiley Periodicals LLC. on behalf of International Society for Advancement of Cytometry. Abstract :